A Tunable Optical Delay Line Based on Cascaded Silicon Nitride Microrings for Ka-Band Beamforming - Dongdong Lin; Xuemeng Xu; Pengfei Zheng; Huimin Yang; Guohua Hu; Binfeng Yun; Yiping Cui (IEEE Photonics Journal)
A continuously tunable optical delay line with low delay ripple based on four cascaded tunable silicon nitride microring resonators for Ka-band beamforming network is proposed. The delay responses of the tunable optical delay line were investigated theoretically and experimentally. And a maximum delay tuning range of 300.3 ps, 169.4 ps and 88.6 ps were achieved when the delay bandwidth is set as 2 GHz, 5 GHz and 10 GHz respectively. In addition, low delay ripple about 8.5 ps and low additional loss less than 3.6 dB were obtained. Moreover, the maximum delay tuning range was increased to about 395 ps by combining the off-resonance region of the cascaded MRRs.